Digestive enzyme expression in the large intestine of children with short bowel syndrome in a late stage of adaptation. Issue 3 (19th January 2020) - de Laffolie, Jan; Sheridan, Diana; Reinshagen, Konrad; Wessel, Lucas; Zimmermann, Christian; Stricker, Sebastian; Lerch, Markus M.; Weigel, Markus; Hain, Torsten; Domann, Eugen; Rudloff, Silvia; Nichols, Buford L.; et al.
Abstract: Background and aims : Intestinal adaptation in short bowel syndrome (SBS) includes morphologic processes and functional mechanisms. This study investigated whether digestive enzyme expression in the duodenum and colon is upregulated in SBS patients. Method : Sucrase‐isomaltase (SI), lactase‐phlorizin hydrolase (LPH), and neutral Aminopeptidase N (ApN) were analyzed in duodenal and colonic biopsies from nine SBS patients in a late stage of adaptation as well as healthy and disease controls by immunoelectron microscopy (IEM), Western blots, and enzyme activities. Furthermore, proliferation rates and intestinal microbiota were analyzed in the mucosal specimen. Results : We found significantly increased amounts of SI, LPH, and ApN in colonocytes in most SBS patients with large variation and strongest effect for SI and ApN. Digestive enzyme expression was only partially elevated in duodenal enterocytes due to a low proliferation level measured by Ki‐67 staining. Microbiome analysis revealed high amounts of Lactobacillus resp. low amounts of Proteobacteria in SBS patients with preservation of colon and ileocecal valve. Colonic expression was associated with a better clinical course in single cases. Conclusion : In SBS patients disaccharidases and peptidases can be upregulated in the colon. Stimulation of this colonic intestinalization process by drugs, nutrients, and pre‐ or probiotics might offer better therapeutic approaches.